UNDERSTANDING THE PROCESS OF SUCCESSFUL CROSS-CULTURAL COUNSELING IN THE CULTURAL DIFFERENCES OF COUNSELEE AND COUNSELORS - Wanda, Nadira Putri; a, asbi; Pradisty, Nabawi; Surbakti, Wahyu Persadanta (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
The purpose of this research is to determine the competencies that a counselor must have in an effort to handle cultural differences between clients and counselors in a counseling process. Where the counselor and counselee hope that the counseling process will run smoothly and get results regarding the handling of the problem being addressed. The writing method in this article uses the concept of literature review technique. It was found in the literature review that there is a connection between culture and counseling. Culture influences several things, namely communication, characteristics, ethics, etc. In dealing with this problem counselors are required to have extensive knowledge about the culture that exists in Indonesia. The counselor is also expected to be able to make the client understand the counselor's own culture to eliminate any cultural bias between the counselee and the counselor. It is not only the counselor who deals with the client's culture, but the client is also expected to be able to understand the counselor's culture. Key Words: culture, counseling, cross-cultural.